Analysis and Design of a New Single Switch Non-Isolated Buck-Boost dc-dc Converter - M. R. Banaei (Journal of Operation and Automation in Power Engineering, 2020)
In this paper, a new transformerless buck-boost converter based on ZETA converter is introduced. The proposed converter has the ZETA converter advantages such as, buck-boost capability and input to output DC insulation. The suggested converter voltage gain is higher than the classic ZETA converter. In the presented converter, only one main switch is utilized. The proposed converter offers low voltage stress of the switch; therefore, the low on-state resistance of the main switch can be selected to decrease losses of the switch. The presented converter topology is simple; hence, the control of the converter is simple. The mathematical analyses of the proposed converter are given. The experimental results confirm the correctness of the analysis.